2001
DOI: 10.1023/a:1010608000074
|View full text |Cite
|
Sign up to set email alerts
|

Methyl‐substituted diindolylmethanes as inhibitors of estrogen‐induced growth of T47D cells and mammary tumors in rats

Abstract: Diindolylmethane (DIM) is formed by acid catalyzed dimerization of the phytochemical indole-3-carbinol, and both compounds inhibit formation and/or growth of mammary tumors in rodents. In this study, we have investigated the aryl hydrocarbon receptor (AhR) agonist activity and inhibitory AhR-estrogen receptor crosstalk induced by the following methyl-substituted DIMs: 1,1'-dimethyl-, 2,2'-dimethyl-, 5,5'-dimethyl-, 6,6'-dimethyl-, and 7,7'-dimethylDIM and 1,1',2,2'-tetramethylDIM. The six compounds bound to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 26 publications
1
55
0
Order By: Relevance
“…All experiments were performed in triplicate and results are presented as mean+standard error of mean (6+s.e.m.) DIM components, which are reported to exhibit anticarcinogenic activity in vitro and in experimental models of mammary tumors (Kojima et al, 1994;McDougal et al, 2001;Morse et al, 1990;Stoewsand et al, 1988;Wattenberg and Loub, 1978). We Figure 6 The in vitro effects of TCDD on pancreatic cancer cell growth as described in Materials and methods.…”
Section: Discussionmentioning
confidence: 99%
“…All experiments were performed in triplicate and results are presented as mean+standard error of mean (6+s.e.m.) DIM components, which are reported to exhibit anticarcinogenic activity in vitro and in experimental models of mammary tumors (Kojima et al, 1994;McDougal et al, 2001;Morse et al, 1990;Stoewsand et al, 1988;Wattenberg and Loub, 1978). We Figure 6 The in vitro effects of TCDD on pancreatic cancer cell growth as described in Materials and methods.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,[35][36][37][38][39][40][41][42][43][44][45][46][47] Liu's group, for example, showed that ICZ exhibits both antiestrogenic and estrogenic activity. 44 I3C and its acid-derived condensation product, ICZ, bound to the aryl hydrocarbon (Ah) receptor and induced cytochrome p450 (CYP)1A1/1A2 gene expression in both in vivo and in vitro models.…”
Section: I3c Modulates the Estrogen Receptormentioning
confidence: 99%
“…4 Their study demonstrated that methyl-substituted DIMs are selective AhR modulators (SAhRMs) with potential for clinical treatment of breast cancer.…”
Section: I3c Modulates the Estrogen Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…3,3'-arylmethylene bis-1H-Indole and its derivatives are well known and an important class of heterocyclic compounds which are used in pharmaceuticals as bioactive intermediates, agrochemicals and in material science. 1 They exhibit a broad spectrum of biological activities such as antimicrobial and antifungal, 2 antibacterial, 3 antitumor, 4 and antioxidantetc agents. 5 Recently, bis (5-methoxy-3-indolyl) methanes have been used as DNA-based electrochemical biosensors that considerably reduce the growth of cancer cell lines such as HOP-92 (lung), A498 (renal), and MDAMB-231/ITCC (breast).…”
Section: Introductionmentioning
confidence: 99%